Multi-scale Holocene Asian monsoon variability deduced from a twin-stalagmite record in southwestern China. Issue 1 (July 2016) - Huang, Wei; Wang, Yongjin; Cheng, Hai; Edwards, Richard Lawrence; Shen, Chuan-Chou; Liu, Dianbing; Shao, Qingfeng; Deng, Chao; Zhang, Zhenqiu; Wang, Quan
Abstract: We present two isotopic (δ 18 O and δ 13 C) sequences of a twin-stalagmite from Zhuliuping Cave, southwestern China, with 230 Th dates from 14.6 to 4.6 ka. The stalagmite δ 18 O record characterizes orbital- to decadal-scale variability of Asian summer monsoon (ASM) intensity, with the Holocene optimum period (HOP) between 9.8 and 6.8 ka BP which is reinforced by its co-varying δ 13 C data. The large multi-decadal scale amplitude of the cave δ 18 O indicates its high sensitivity to climate change. Four centennial-scale weak ASM events during the early Holocene are centered at 11.2, 10.8, 9.1 and 8.2 ka. They can be correlated to cold periods in the northern high latitudes, possibly resulting from rapid dynamics of atmospheric circulation associated with North Atlantic cooling. The 8.2 ka event has an amplitude more than two-thirds that of the Younger Dryas (YD), and is significantly stronger than other cave records in the Asia monsoon region, likely indicating a more severe dry climate condition at the cave site. At the end of the YD event, the δ 13 C record lags the δ 18 O record by 300–500 yr, suggesting a multi-centennial slow response of vegetation and soil processes to monsoon enhancement.